Whole food for your family : 100+ simple, budget-friendly meals - Michaelis, Autumn (Mariner Books, 2022)
"Over 100 budget--and family--friendly recipes from Whole30 Coach and creator of the popular cooking website Whole Food for 7, Autumn Michaelis. This inspired collection is dairy-free, gluten-free, and fully endorsed by Whole30! Changing the way your family eats can feel intimidating, but once Autumn Michaelis experienced the incredible benefits of the Whole30 and cut gluten, dairy, and refined sugar out of her life, she knew she had to bring her family on board. As a busy mother of 5--yes, 5--growing boys, she needed recipes that were tasty and easy. So she started the website Whole Food for 7, where she shares no-fuss, gluten- and dairy- free family meals that are delicious and nutritious. In her first cookbook, she serves up winning breakfasts like Crispy Waffles, lunch box essentials like Paleo Vanilla Wafers and Granola Bars, healthy remakes of kid favorites like Plantain Pizza Pockets and Our Favorite Chicken Strips, along with plenty of desserts like Churro Bites and Oreo Brownie Cheesecake. Kid-friendly, but not just for kids, this book is packed with comfort food favorites as well as time-saving hacks, and budget-friendly tips. Whole Food for Your Family is destined to become your go-to cookbook every day of the week." --